Key issues in education policy - Ward, Stephen, 1947-; Eden, Christine; Sage eBooks (London : SAGE, 2009)
This work looks at state involvement in education and education policy. It explains the role of education policy in the context of the general direction of government policy, politics and the economy.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Education and state -- Great Britain; Education -- Political aspects -- Great Britain; Electronic books